Evaluating the Impact of Export Finance Support on Firm-Level Export Performance: Evidence from Pakistan - Fabrice Defever; Alejandro Ria\~no; Gonzalo Varela (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper evaluates the impact of two export finance support schemes: The Export Finance Scheme (EFS) and the Long-Term Finance Facility for Plant & Machinery (LTFF) on firm-level export performance. These policies offer loans to exporters at concessionary interest rates to finance short-term working capital and long-term investment in machinery and equipment respectively. To do so, we combine customs data with information about which firms participate in each scheme and the value of the loans they obtain between 2015 and 2017. We find that EFS and LTFF increased the growth rate of exports sales by 7 and 8-11 percentage points respectively. Neither policy exerts a significant impact on the number of products that a firm exports or the number of foreign countries it sells to. Our analysis indicates that facilitating long-term investment in physical capital is more cost effective to raise exports than subsidizing exporters' working capital needs.
Keywords: G21; G28; G32; F13; F65; 330; trade finance; export credit; export subsidies; export margins; Pakistan